Adaptive optimization of crop production and nitrogen leaching abatement under yield uncertainty - Hyytiäinen, Kari; Niemi, Jarkko K.; Koikkalainen, Kauko; Palosuo, Taru; Salo, Tapio (Elsevier, 2011)
The study develops a bio-economic crop management model that internalizes the environmental cost of nitrate pollution, accounts for stochastic weather, and includes an option for split fertilization. The integrated model is designed to indicate whether a producer can benefit from applying fertilizer several times during the growing season, in response to crop needs, rather than a single time, at sowing. The model is parameterized for the cultivation of spring malting barley (Hordeum vulgare L.) in Southern Finland. The costs of negative externalities from nitrogen leaching are internalized in the landowner s decision problem through a pollution tax. The results indicate that without a pollution tax a single application of fertilizer gauged to meet the needs of the entire season is optimal. With a tax, the benefits of split application applying varying amounts of fertilizer at selected stages of the growing season increase significantly. In comparison to a single application of fertilizer at sowing, split fertilization improves yields, increases the total amount of fertilizer used, and reduces nitrogen leaching.
Keywords: Ma; lannoitus; typpilannoitus; huuhtoutuminen; fertilization; nitrogen; leaching; pollution tax; stochastic dynamic programming